An investigation of South African attitudes towards online shopping - Stander, Chelsea (The IIE, 2018)
The South African online retail sector has been growing steadily over the past few years, however there is still some reluctant consumers. Given the competition among shopping channels and the resistance towards online shopping, this study’s aim was to identify the reasons that drive Internet users to buy or avoid buying off the Internet. The Online Shopping Acceptance Model (OSAM) was the main theory considered for this research study, therefore one of the main perspectives observed in this study was demographics. Using an online survey of 25 shoppers, this study revealed that people who shop online do not necessarily trust online shopping, and people who do not shop online do not necessarily distrust online shopping and vice versa. This study used a chi-square test to calculate the critical value and the results were not significant, and therefore did not reject the null hypothesis. Reasons for trusting online shopping was due to recommendations (word of mouth), trusting the brand, a good rating on the site, the details on the site, and if the website was of a good quality. In addition, the most common reason for shopping online was due convenience.
Keywords: Online Shopping Acceptance Model (OSAM); online retail; Internet users; South African attitudes; demographic factors